Solid waste-based 3D printing concrete and preparation method thereof

By using solid waste materials such as modified tungsten tailings and steel slag in 3D printed concrete, combined with specific formulas and preparation methods, the shortcomings in existing 3D printed concrete in terms of strength and fluidity are solved, and an efficient and environmentally friendly 3D printing process and material performance improvement are achieved.

CN119613042APending Publication Date: 2025-03-14SHANGHAI MCC ENVIRONMENTAL ENG TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411752922.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing 3D printed concrete does not perform well in terms of strength and fluidity, and prints are prone to clogging, which cannot meet the needs of 3D printing technology for rapid molding and efficient construction of materials.

Method used

By mixing cement, mineral powder, modified tungsten tailings, steel slag, tungsten tailings sand, composite fiber, dispersible latex powder, water reducing agent, early strength agent, retarder and water in a specific proportion, and the preparation method of modified tungsten tailings is adopted, including ultrasonic heating soaking, filtration, drying, ball milling and screening in alkaline solution, the modified tungsten tailings is obtained to enhance the gelling mechanical strength of the concrete.

Benefits of technology

The high strength, good fluidity and smooth printing process of 3D printed concrete are realized, reducing the risk of blockage, and improving the utilization rate of solid waste, reducing resource consumption and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165449800000071
    Figure BDA0005165449800000071
  • Figure BDA0005165449800000091
    Figure BDA0005165449800000091
Patent Text Reader

Abstract

The invention relates to the technical field of concrete preparation, in particular to solid waste based 3D printing concrete which comprises the following raw materials: cement, mineral powder, modified tungsten tailings, water glass, steel slag, tungsten tailing sand, composite fibers, dispersible latex powder, a water reducing agent, an early strength agent, a retarder and water. The preparation method comprises the following steps: mixing the cement, the mineral powder and the modified tungsten tailing powder to obtain a cementing material component A; mixing steel slag, tungsten tailing sand, dispersible latex powder, an early strength agent, a retarder and composite fibers to obtain a solid component B; adding a water reducing agent and water glass into water, diluting and uniformly stirring to obtain a liquid component C; adding the solid component B and part of the cementing material component A, stirring, then adding part of the liquid component C, mixing, adding the rest of the cementing material component A, adding the rest of the liquid component C, and stirring again to obtain the 3D printing concrete. The prepared concrete is good in mechanical property, and solid waste cooperative treatment is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete preparation, and in particular to solid waste-based 3D printed concrete and a preparation method thereof. Background Art

[0002] 3D printed concrete is a new type of building material that is made by stacking specific concrete materials layer by layer through 3D printing technology. This technology combines digital design, material science and precision machinery technology, and can achieve high-precision and high-efficiency construction in complex structural construction. It has the advantages of high precision, high degree of freedom in design, green environmental protection, energy saving and material saving. It can be applied to walls, art sculptures, municipal supporting building components, etc.

[0003] 3D concrete printing technology is of great significance to the construction industry and can bring many benefits, such as building special-shaped buildings, shortening construction time, reducing carbon emissions, and reducing labor and construction costs. At the same time, 3D concrete printing technology also faces various challenges, and it is necessary for the construction industry to conduct in-depth research in this field in order to better utilize this new technology.

[0004] At present, ordinary concrete or high-performance concrete used in construction cannot meet the requirements, because 3D printing requires concrete materials to have rapid molding properties. After the concrete material flows out of the printer, it must be able to "stand up" immediately and cannot continue to flow, that is, it must have excellent thixotropic properties (higher plastic viscosity, lower ultimate shear stress, rapid rheology once stirred, and rapid standing of the concrete once it flows out). At the same time, it should have a faster setting time and higher early strength. Otherwise, the printed structure size will deviate greatly from the initial design, and the lower concrete cannot be deformed during the continuous stacking process.

[0005] At the same time, in response to the problems of huge amount of construction waste, serious solid waste pollution and low added utilization value in my country, by combining solid waste materials with 3D printing technology, efficient recycling of solid waste is achieved and the cost of 3D printed concrete is reduced.

[0006] The invention patent application CN110540394A discloses "a material suitable for 3D printing concrete shear wall and its preparation method". The patent adopts polypropylene short fibers. If the short fibers are used to achieve appropriate tensile strength, the fiber amount needs to be increased. Once the fiber amount is increased, the blockage rate of printing will increase, which is not conducive to printing. In addition, the patent is mixed with quicklime, which has the characteristic of releasing a large amount of heat when it comes into contact with water, which may increase the cracking rate of the sample after printing.

[0007] Therefore, there is an urgent need to provide a 3D printed concrete that has good strength, good fluidity, no clogging during printing, and can improve the utilization rate of solid waste. Summary of the invention

[0008] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a solid waste-based 3D printed concrete and a preparation method thereof, so as to solve the problems of poor strength and fluidity of 3D printed concrete in the prior art, and easy clogging during printing, and to provide a method for applying solid waste as raw material in 3D printed concrete, thereby improving the utilization rate of solid waste.

[0009] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.

[0010] The first aspect of the present invention is to provide a solid waste-based 3D printing concrete, the concrete comprising the following raw materials in parts by weight: 18-22 parts of cement, 5-10 parts of mineral powder, 8-12 parts of modified tungsten tailings, 3-6 parts of water glass, 18-24 parts of steel slag, 16-22 parts of tungsten tailings sand, 1-3 parts of composite fiber, 0.8-2 parts of dispersible latex powder, 0.6-1 parts of water reducer, 0.4-0.8 parts of early strength agent, 0.2-0.3 parts of retarder, and 9-16 parts of water. The preparation method of the modified tungsten tailings comprises the following steps:

[0011] A1. Add tungsten tailings into alkaline solution and soak them by ultrasonic heating;

[0012] A2. Filter out the tungsten tailings, rinse, dry, ball mill and sieve to obtain modified tungsten tailings.

[0013] The second aspect of the present invention is to provide a method for preparing solid waste-based 3D printed concrete, comprising the following steps:

[0014] S1. Mix cement, mineral powder and modified tungsten tailings powder to obtain a cementitious material component A;

[0015] S2, mixing steel slag, tungsten tailings, dispersible latex powder, early strength agent, retarder, and composite fiber to obtain a solid component B;

[0016] S3, adding water reducing agent and water glass into water, diluting and stirring evenly to obtain liquid component C;

[0017] S4. First add solid component B and part of cementitious material component A, stir, then add part of liquid component C, mix, then add the remaining cementitious material component A and add the remaining liquid component C at a uniform speed and stir again to obtain 3D printed concrete.

[0018] As described above, the solid waste-based 3D printed concrete and the preparation method thereof of the present invention have the following beneficial effects:

[0019] (1) The present invention combines mining solid waste such as slag, steel slag, and tungsten tailings to prepare 3D printed concrete, which not only achieves coordinated management of solid waste, but also saves resources such as cement and quartz sand, which is conducive to the construction of a "zero-waste city".

[0020] (2) The 3D printing concrete material prepared by the present invention using steel slag, slag powder, modified tungsten tailings, and tungsten tailings sand has good extrudability and constructability, and can smoothly carry out the construction 3D printing process. The concrete has suitable fluidity and setting time, and has good mechanical properties after drying. DETAILED DESCRIPTION

[0021] In order to make the purpose of the invention, technical solutions and beneficial technical effects of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. People familiar with this technology can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0022] Tungsten tailings are solid materials formed by dehydration of fine tailings slurry after the tungsten-containing minerals are selected after grinding tungsten ore. They are generally composed of gangue minerals and surrounding rock minerals, mainly containing fluorite, quartz, garnet, feldspar, mica, calcite and other minerals. According to the current tungsten ore grade and mineral processing technology, about 8 tons of tungsten tailings are produced for every 1 ton of tungsten concentrate produced. The stock and annual increase of tungsten tailings in my country are huge. With the country's restrictions on the construction of new tailings ponds, the existing tailings ponds will face closure in the next 3 to 10 years. At that time, tungsten mining companies will face the situation of having nowhere to pile tailings. If the tailings are placed on the surface, they will occupy a large amount of land resources and pose certain potential hazards to the environment, thereby endangering human health.

[0023] The first aspect of the present invention is to provide a solid waste-based 3D printing concrete, the concrete comprising the following raw materials in parts by weight: 18-22 parts of cement, 5-10 parts of mineral powder, 8-12 parts of modified tungsten tailings, 3-6 parts of water glass, 18-24 parts of steel slag, 16-22 parts of tungsten tailings sand, 1-3 parts of composite fiber, 0.8-2 parts of dispersible latex powder, 0.6-1.0 parts of water reducer, 0.4-0.8 parts of early strength agent, 0.2-0.3 parts of retarder, and 9-16 parts of water. The preparation method of the modified tungsten tailings comprises the following steps:

[0024] A1. Add tungsten tailings into alkaline solution and soak them by ultrasonic heating;

[0025] A2. Filter out the tungsten tailings, rinse, dry, ball mill and sieve to obtain modified tungsten tailings.

[0026] The tungsten tailings added in the present invention are used as high-silicon-aluminum materials. They are subjected to hydrothermal activation and alkaline corrosion treatment by hot dipping in a saturated alkaline solution, and their surfaces are corroded and a large amount of flocculent sediments are produced to form CSH gel. The modified tungsten tailings are further obtained by mechanical grinding and physical excitation to improve the activity of the tungsten tailings. The cement-slag powder-modified tungsten tailings gelling material is further alkali-excited with water glass. Under the action of the alkali activator, Si-O and Al-O in the system are broken, and the active silicon-aluminum components are dissolved to generate a large amount of low-polymerized silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons, which are dehydrated and condensed into a network of Si-O-Al polymer structures, thereby improving the cementitious mechanical strength of the concrete. The steel slag aggregate contains active dicalcium silicate and tricalcium silicate, which can participate in the alkali excitation reaction in the modified tungsten tailings. At the same time, the rough surface of the steel slag has good adhesion to the concrete, which helps to improve the strength of the concrete.

[0027] Modified tungsten tailings act as a cementitious material similar to cement, while tungsten tailings sand acts as concrete aggregate.

[0028] Polypropylene fiber has low density and can effectively reduce the overall weight of concrete, improve the toughness and impact resistance of concrete, and is suitable for structures subjected to dynamic loads to reduce the possibility of brittle failure. Basalt fiber has excellent strength and stiffness. Under cyclic loads, basalt fiber can enhance the fatigue performance of concrete. The combined use of the two can give full play to their respective advantages. The addition of polypropylene fiber can improve the workability of concrete, while basalt fiber enhances the constructability of concrete. In addition, the cost of basalt fiber is relatively high, but through the combined use, it can optimize cost-effectiveness while improving performance.

[0029] The present invention uses steel slag and modified tungsten tailings to prepare a high-strength 3D printing concrete; on the one hand, it can absorb metallurgical slag and tailings solid waste; on the other hand, it turns waste into treasure to prepare a high-strength 3D printing concrete material.

[0030] In some embodiments of the present invention, the concrete includes the following raw materials in parts by weight: 18-20 parts of cement, 5-8 parts of mineral powder, 8-10 parts of modified tungsten tailings, 3-5 parts of water glass, 18-20 parts of steel slag, 16-19 parts of tungsten tailings sand, 1-2 parts of composite fiber, 0.8-1.5 parts of dispersible latex powder, 0.6-0.8 parts of water reducer, 0.4-0.6 parts of early strength agent, 0.2-0.3 parts of retarder, and 9-13 parts of water.

[0031] In some embodiments of the present invention, the concrete includes the following raw materials in parts by weight: 20-22 parts of cement, 8-10 parts of mineral powder, 10-12 parts of modified tungsten tailings, 5-6 parts of water glass, 20-24 parts of steel slag, 19-22 parts of tungsten tailings sand, 2-3 parts of composite fiber, 1.5-2 parts of dispersible latex powder, 0.8-1.0 parts of water reducer, 0.6-0.8 parts of early strength agent, 0.2-0.3 parts of retarder, and 13-16 parts of water.

[0032] In some embodiments of the present invention, the concrete includes the following raw materials in parts by weight: 18 parts of cement, 5 parts of mineral powder, 8 parts of modified tungsten tailings, 3 parts of water glass, 18 parts of steel slag, 16 parts of tungsten tailings sand, 1 part of composite fiber, 0.8 parts of dispersible latex powder, 0.6 parts of water reducer, 0.4 parts of early strength agent, 0.2 parts of retarder, and 9 parts of water.

[0033] In some embodiments of the present invention, the concrete includes the following raw materials in parts by weight: 20 parts of cement, 8 parts of mineral powder, 10 parts of modified tungsten tailings, 5 parts of water glass, 22 parts of steel slag, 19 parts of tungsten tailings sand, 2 parts of composite fiber, 1.5 parts of dispersible latex powder, 0.8 parts of water reducer, 0.6 parts of early strength agent, 0.3 parts of retarder, and 13 parts of water.

[0034] In some embodiments of the present invention, the concrete includes the following raw materials in parts by weight: 22 parts of cement, 10 parts of mineral powder, 12 parts of modified tungsten tailings, 6 parts of water glass, 24 parts of steel slag, 22 parts of tungsten tailings sand, 3 parts of composite fiber, 2 parts of dispersible latex powder, 1.0 part of water reducer, 0.8 part of early strength agent, 0.3 part of retarder, and 16 parts of water.

[0035] In some embodiments of the present invention, the particle size of the tungsten tailings in step A1) is 0.15-1.5 mm; specifically, the particle size can be 0.15-0.85 mm or 0.85-1.5 mm.

[0036] In some embodiments of the present invention, the molar concentration of the alkaline solution in step A1) is 3-5 mol / L; specifically, the molar concentration may be 3 mol / L, 4 mol / L, or 5 mol / L.

[0037] In some embodiments of the present invention, the alkaline solution in step A1) can be any alkaline solution commonly used in the art. In some examples, the alkaline solution is selected from one or more of sodium hydroxide solution, potassium hydroxide solution, and sodium carbonate solution; preferably, the alkaline solution is sodium hydroxide solution.

[0038] In some embodiments of the present invention, the soaking temperature in step A1) is 65-90°C; the soaking time is 2-4h; specifically, the soaking temperature can be 65-80°C, 80-90°C; typically but not limitatively, for example, 65°C, 80°C, 90°C; the soaking time can be 2-3h, 3-4h, typically but not limitatively, for example, 2h, 3h, 4h.

[0039] In some embodiments of the present invention, the frequency of ultrasound in step A1) is 20-30 kHz, and the power is 800-900 W.

[0040] In some embodiments of the present invention, the particle size of the modified tungsten tailings in step A2) is 200-325 mesh; specifically, the particle size of the modified tungsten tailings can be 200-280 mesh or 280-325 mesh.

[0041] In some embodiments of the present invention, the rinsing time in step A2) is 1-3 minutes; the drying temperature is 100-110°C, and the drying time is 4-6 hours. Specifically, the drying temperature can be 100-105°C, 105-110°C, typically but not limiting, for example, 100°C, 105°C, 110°C. The drying time can be 4-5h, 5-6h; typically but not limiting, for example, 4h, 5h, 6h.

[0042] In some embodiments of the present invention, the present invention has no special limitation on the source and requirements of cement, and commercially available products of cement frequently used by those skilled in the art may be used. Specifically, the cement of the present invention may be PO 42.5 ordinary Portland cement, and the manufacturer is Taicang Conch Cement Co., Ltd.

[0043] In some embodiments of the present invention, the present invention has no special restrictions on the source and requirements of the mineral powder, and commercially available cement products commonly used by those skilled in the art can be used. Specifically, the mineral powder of the present invention is S95 mineral powder, and the density of the mineral powder is ≥2.8g / cm 3 .Specific surface area ≥350m 2 / kg, 28d activity index ≥95%; the manufacturer of the mineral powder may be Baotian New Building Materials Co., Ltd.

[0044] In some embodiments of the present invention, the present invention has no special limitation on the source and requirements of water glass, and commercially available water glass products frequently used by technicians in this field can be used. Specifically, the modulus of the water glass of the present invention is 2.5, and the manufacturer is Jiashan Jinghua New Material Technology Co., Ltd.

[0045] In some embodiments of the present invention, the steel slag is selected from any one of electric furnace drum steel slag and converter steel slag; the particle size of the steel slag is 0.8-4mm, and the f.CaO content in the steel slag is less than 1%; the present invention has no special limitation on the source and requirements of the electric furnace drum steel slag, and the commercially available products of the electric furnace drum steel slag frequently used by those skilled in the art can be used. The present invention has no special limitation on the source and requirements of the converter steel slag, and the commercially available products of the converter steel slag frequently used by those skilled in the art can be used.

[0046] In some embodiments of the present invention, the present invention has no special limitation on the source and requirements of tungsten tailings sand, and commercially available products of tungsten tailings sand frequently used by technicians in this field can be used. Specifically, the particle size of the tungsten tailings sand of the present invention is 0.15-1.5mm; the manufacturer is Hunan Nonferrous Xintianling Tungsten Industry Co., Ltd.

[0047] In some embodiments of the present invention, the composite fiber includes polypropylene fiber and basalt fiber; the composite fiber is composed of polypropylene fiber and basalt fiber in a mass ratio of 5-7:3-4; the addition of the composite fiber facilitates the formation of a three-dimensional skeleton between the composite fiber and the concrete raw materials, thereby improving the strength of the concrete.

[0048] In some embodiments of the present invention, the polypropylene fiber has a diameter of 35-45 μm and a length of 3-12 mm;

[0049] In some embodiments of the present invention, the basalt fiber has a diameter of 10-20 μm and a length of 8-15 mm;

[0050] In some embodiments of the present invention, the dispersible latex powder is polyvinyl alcohol dispersible latex powder, with a solid content of ≥98%, a pH of 6-8, and a minimum film-forming temperature of 0-5° C. The present invention has no special limitation on the source of the dispersible latex powder, and commercially available products of dispersible latex powders frequently used by those skilled in the art can be used.

[0051] In some embodiments of the present invention, the present invention has no requirements for the water reducer, and the water reducer commonly used in the art can be used. Specifically, the water reducer is selected from one or more of polycarboxylic acid-based high-efficiency water reducers, melamine-based high-efficiency water reducers, and lignin sulfonate water reducers; preferably, the water reducer is a polycarboxylic acid-based high-efficiency water reducer, and the manufacturer is Suzhou Easy Building Materials Technology Co., Ltd.

[0052] In some embodiments of the present invention, the early strength agent is selected from one or more of anhydrous sodium sulfate, triethanolamine, and calcium chloride.

[0053] In some embodiments of the present invention, the retarder is selected from one or more of sodium gluconate, citric acid, and molasses.

[0054] The second aspect of the present invention is to provide a method for preparing solid waste-based 3D printed concrete as described in any one of the above, comprising the following steps:

[0055] S1. Mix cement, mineral powder and modified tungsten tailings powder to obtain a cementitious material component A;

[0056] S2, mixing steel slag, tungsten tailings, dispersible latex powder, early strength agent, retarder, and composite fiber to obtain a solid component B;

[0057] S3, adding water reducing agent and water glass into water, diluting and stirring evenly to obtain liquid component C;

[0058] S4. First add solid component B and part of cementitious material component A, stir, then add part of liquid component C, mix, then add the remaining cementitious material component A and add the remaining liquid component C at a uniform speed and stir again to obtain 3D printed concrete.

[0059] In some embodiments of the present invention, the mixing time in step S1 is 35-50 seconds.

[0060] In some embodiments of the present invention, the mixing time in step S2 is 25-35 seconds.

[0061] In some embodiments of the present invention, the stirring time in step S4 is 25-35 s, and the mixing time is 20-30 s.

[0062] In some embodiments of the present invention, the stirring time in step S4 is 135-185 seconds.

[0063] The present invention is further described below by way of examples, but the scope of the present invention is not limited thereto.

[0064] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. If specific conditions are not specified in the embodiment, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for all reagents or instruments, they are conventional products that can be purchased commercially. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any method, equipment, and material of the prior art similar or equivalent to the method, equipment, and material in the embodiments of the present invention can also be used to realize the present invention.

[0065] Preparation example of modified tungsten tailings

[0066] Preparation Example 1

[0067] This preparation example provides a preparation method of modified tungsten tailings, comprising the following steps:

[0068] A1. Add 0.15-1.5 mm tungsten tailings into 4 mol / L sodium hydroxide solution at 85 degrees Celsius, and heat and soak in a 25kHz ultrasonic reactor for 3 hours;

[0069] A2. Filter out the tungsten tailings and rinse them with tap water for 1 minute, then put them into a drying oven and dry them at 105℃ for 5 hours; grind the dried tungsten tailings with a ball mill and sieve them to obtain modified tungsten tailings with mesh sizes of 200 to 325.

[0070] Example

[0071] Table 1 Ratio of components of solid waste-based 3D printing concrete raw materials in Examples 1-5 and Comparative Examples 1-3

[0072]

[0073]

[0074] Example 1

[0075] This embodiment provides a solid waste-based 3D printing concrete, the raw material composition ratio is shown in Table 1, the concrete includes the following raw materials in parts by weight: 18 parts of cement, 8 parts of mineral powder, 12 parts of modified tungsten tailings, 6 parts of water glass, 18 parts of steel slag, 22 parts of tungsten tailings sand, 2 parts of composite fiber, 1.5 parts of dispersible latex powder, 0.65 parts of water reducer, 0.4 parts of early strength agent, 0.2 parts of retarder, and 9 parts of water. The modified tungsten tailings are prepared in Preparation Example 1. The cement is PO 42.5 ordinary silicate cement, and the manufacturer is Taicang Conch Cement Co., Ltd.; the mineral powder is S95 mineral powder, and the density is not less than 2.8g / cm 3 , with a specific surface area of ​​not less than 350m 2 / kg, 28d activity index is not less than 95%, the manufacturer is Baotian New Building Materials Co., Ltd.; the water glass, modulus is 2.5, the manufacturer is Jiashan Jinghua New Materials Technology Co., Ltd.; the steel slag is electric furnace drum steel slag with a particle size of 0.8-4mm, provided by Shanghai MCC Environmental Engineering Technology Co., Ltd., and its f.CaO (free calcium) content is less than 1%; the tungsten tailings sand is 0.15-1.5mm, the manufacturer is Hunan Nonferrous Xintianling Tungsten Industry Co., Ltd.; the composite fiber is composed of polypropylene fiber and basalt fiber in a mass ratio of 6:4, the diameter of the polypropylene fiber is 40μm, The length is 3-12mm, the diameter of the basalt fiber is 15μm, and the length is 8-15mm; the manufacturer is Changzhou Tianyi Engineering Fiber Co., Ltd.; the dispersible latex powder is polyvinyl alcohol dispersible latex powder, with a solid content of ≥98%, a pH of 6-8, and a minimum film-forming temperature of 0-5°C, and the manufacturer is Shanghai Hengchuang Chemical Co., Ltd.; the water reducer is a polycarboxylic acid-based high-efficiency water reducer, Suzhou Yiste Building Materials Technology Co., Ltd.; the early strength agent is an industrial-grade anhydrous sodium sulfate early strength agent, Shanghai Qiren Chemical Co., Ltd.; the retarder is an industrial-grade sodium grape carbonate retarder, Suzhou Duoyuan Chemical Co., Ltd.

[0076] This embodiment provides a method for preparing solid waste-based 3D printed concrete, comprising the following steps:

[0077] S1. Put cement, mineral powder and modified tungsten tailings powder into a stirrer and stir for 45 seconds to mix them evenly to obtain cementitious material component A;

[0078] S2, put steel slag, tungsten tailings, dispersible latex powder, early strength agent, retarder, and composite fiber into a stirrer and stir for 30 seconds to mix evenly to obtain a solid component B;

[0079] S3, adding water reducing agent and water glass into water, diluting and stirring evenly to obtain liquid component C;

[0080] S4, first add solid component B and 1 / 2 of cementitious component A, stir for 30 seconds, then add 1 / 2 of liquid component C, mix in the mixer for 25 seconds, then add the remaining cementitious component A and the remaining liquid component C at a uniform speed and stir again for 180 seconds to obtain 3D printed concrete. Here, 1 / 2 of cementitious component A means 1 / 2 of the total amount of cementitious component A, and here, 1 / 2 of liquid component C means 1 / 2 of the total amount of liquid component C.

[0081] Example 2

[0082] This embodiment provides a solid waste-based 3D printing concrete, and the raw material composition ratio is shown in Table 1. The difference from Embodiment 1 is that the raw material composition ratio is different.

[0083] Example 3

[0084] This embodiment provides a solid waste-based 3D printing concrete, and the raw material composition ratio is shown in Table 1. The difference from Embodiment 1 is that the raw material composition ratio is different.

[0085] Example 4

[0086] This embodiment provides a solid waste-based 3D printing concrete, and the raw material composition ratio is shown in Table 1. The difference from Embodiment 1 is that the raw material composition ratio is different.

[0087] Example 5

[0088] This embodiment provides a solid waste-based 3D printing concrete, and the raw material composition ratio is shown in Table 1. The difference from Embodiment 1 is that the raw material composition ratio is different.

[0089] Comparative Example

[0090] Comparative Example 1

[0091] This comparative example provides a solid waste-based 3D printing concrete, and the raw material composition ratio is shown in Table 1. The difference from Example 1 is that: this comparative example does not add modified tungsten tailings, and the amount of tungsten tailings sand added is different from that in Example 1.

[0092] Comparative Example 2

[0093] This comparative example provides a solid waste-based 3D printing concrete, and the raw material composition ratio is shown in Table 1. The difference from Example 1 is that: this comparative example does not add tungsten tailings sand, and the amount of steel slag added is different from that in Example 1.

[0094] Comparative Example 3

[0095] This comparative example provides a solid waste-based 3D printing concrete, and the raw material composition ratio is shown in Table 1. The difference from Example 1 is that: this comparative example does not add steel slag, and the amount of tungsten tailings added is different from that in Example 1.

[0096] Performance Testing

[0097] Concrete fluidity test: The concretes prepared in Examples 1-5 and Comparative Examples 1-3 were tested for fluidity according to the test method in GB / T 2419-2005 “Method for determination of fluidity of cement mortar”. The test results are shown in Table 2.

[0098] Apparent morphology test: The concretes prepared in Examples 1-5 and Comparative Examples 1-3 were observed to observe the buildability and extrudability of the corresponding concretes. The observation results are shown in Table 2.

[0099] Concrete setting performance test: The concrete prepared in Examples 1-5 and Comparative Examples 1-3 was taken, and the setting time of the concrete was tested according to the test method in JGJ / T 70-2009 "Standard for Test Methods for Basic Properties of Building Mortar". The test results of the setting time are shown in Table 2.

[0100] Concrete strength performance test: The concrete prepared in Examples 1-5 and Comparative Examples 1-3 was taken, and the interlaminar splitting strength and dry compressive strength of the concrete were tested according to the test method in T / CECS 786-2020 "Technical Specification for Concrete 3D Printing". The test results are shown in Table 2.

[0101] Table 2 Performance test results of solid waste-based 3D printed concrete in Examples 1-5 and Comparative Examples 1-3

[0102]

[0103] In combination with Examples 1-5 and the data in Table 2, it can be seen that the solid waste-based 3D printed concrete obtained in Examples 1-5 has good fluidity, exceeding 170 mm, and after extrusion, the morphology temperature does not collapse. At the same time, it is continuous and uniform during extrusion, without blockage, and the setting time is short, as low as 41 min. The interlayer splitting strength is large, as high as 5.4 MPa, and the dry compressive strength is good, as high as 54.9 MPa. The overall performance of the solid waste-based 3D printed concrete obtained in Examples 1-5 is better.

[0104] Combining Example 1 and Comparative Example 1, and combining the data in Table 2, it can be seen that the interlaminar splitting strength and dry compressive strength of the concrete prepared in Comparative Example 1 are not as good as those of the concrete prepared in Example 1. The difference between Example 1 and Comparative Example 1 is that: Comparative Example 1 does not add modified tungsten tailings, but increases the amount of tungsten tailings sand added. It can be seen that the addition of modified tungsten tailings helps to improve the interlaminar splitting strength and dry compressive strength of the concrete.

[0105] Combining Example 1 and Comparative Example 2, and combining the data in Table 2, it can be seen that the concrete prepared in Comparative Example 2 has poor fluidity and local deformation problems. During extrusion, the uniformity is poor. The difference between Comparative Example 2 and Example 1 is that no tungsten tailings sand is added to Comparative Example 2, but the amount of steel slag added is increased. It can be seen that the three components of tungsten tailings sand, modified tungsten tailings and steel slag cooperate with each other, and the concrete prepared thereby has better performance in all aspects. If no tungsten tailings sand is added, the extrusion performance of the prepared concrete is poor and the shape is unstable.

[0106] Combining Example 1 and Comparative Example 3, and combining the data in Table 2, it can be seen that the concrete prepared in Comparative Example 3 is prone to local deformation, and the interlaminar splitting strength and dry compressive strength are not good. The difference between Comparative Example 3 and Example 1 is that: Comparative Example 3 does not add steel slag, but at the same time increases the amount of tungsten tailings added. It can be seen that if steel slag is not added, the interlaminar splitting strength and dry compressive strength of the concrete are not good. Example 1 simultaneously adds three components of steel slag, tungsten tailings, and modified tungsten tailings. The addition of steel slag aggregate helps to improve the interlaminar splitting strength and dry compressive strength of 3D concrete.

[0107] In Example 1-5, the 3D printing concrete material prepared by composite using steel slag, slag powder, modified tungsten tailings, and tungsten tailings sand has good extrudability and constructability, and can smoothly carry out the construction 3D printing process. The concrete has appropriate fluidity and setting time, and has good mechanical properties after drying.

[0108] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A solid waste-based 3D printed concrete, characterized in that: The concrete comprises the following raw materials in parts by weight: 18-22 parts of cement, 5-10 parts of mineral powder, 8-12 parts of modified tungsten tailings, 3-6 parts of water glass, 18-24 parts of steel slag, 16-22 parts of tungsten tailings sand, 1-3 parts of composite fiber, 0.8-2 parts of dispersible latex powder, 0.6-1.0 parts of water reducer, 0.4-0.8 parts of early strength agent, 0.2-0.3 parts of retarder, and 9-16 parts of water. The preparation method of the modified tungsten tailings comprises the following steps: A1. Add tungsten tailings into alkaline solution and soak them by ultrasonic heating; A2. Filter out the tungsten tailings, rinse, dry, ball mill and sieve to obtain modified tungsten tailings.

2. The solid waste-based 3D printed concrete according to claim 1, characterized in that: Also includes one or more of the following characteristics: A11) the particle size of the tungsten tailings in step A1) is 0.15-1.5 mm; A12) the molar concentration of the alkaline solution in step A1) is 3-5 mol / L; A13) the alkaline solution in step A1) is selected from one or more of sodium hydroxide solution, potassium hydroxide solution and sodium carbonate solution; A14) the soaking temperature in step A1) is 65-90° C. and the soaking time is 2-4 hours; A15) The frequency of ultrasound in step A1) is 20-30kHz and the power is 800-900W; A21) the particle size of the modified tungsten tailings in step A2) is 200-325 mesh; A22) The rinsing time in step A2) is 1-3 minutes; the drying temperature is 100-110°C, and the drying time is 4-6 hours.

3. The solid waste-based 3D printing concrete according to claim 1, characterized in that: Also includes one or more of the following characteristics: 11) The cement is ordinary Portland cement; 12) The mineral powder is S95 mineral powder, and the density of the mineral powder is ≥2.8g / cm 3 .Specific surface area ≥350m 2 / kg, 28d activity index ≥95%; 13) The modulus of the water glass is 2-4; 14) The steel slag is selected from any one of electric furnace drum steel slag and converter steel slag; 15) The particle size of the steel slag is 0.8-4 mm, and the f.CaO content in the steel slag is less than 1%; 16) The particle size of the tungsten tailings is 0.15-1.5 mm; 17) The composite fiber comprises polypropylene fiber and basalt fiber; 18) The dispersible latex powder is polyvinyl alcohol dispersible latex powder with a solid content of ≥98%, a pH of 6-8, and a minimum film-forming temperature of 0-5°C.

4. The solid waste-based 3D printing concrete according to claim 3, characterized in that: Also includes one or more of the following characteristics: 171) The composite fiber is composed of polypropylene fiber and basalt fiber in a mass ratio of 5-7:3-4; 172) The diameter of the polypropylene fiber is 35-45 μm and the length is 3-12 mm; 173) The diameter of the basalt fiber is 10-20 μm and the length is 8-15 mm.

5. The solid waste-based 3D printing concrete according to claim 1, characterized in that: Also includes one or more of the following characteristics: 21) The water reducer is selected from one or more of polycarboxylic acid-based high-efficiency water reducers, melamine-based high-efficiency water reducers, and lignin sulfonate-based water reducers; 22) The early strength agent is selected from one or more of anhydrous sodium sulfate, triethanolamine and calcium chloride; 23) The retarder is selected from one or more of sodium gluconate, citric acid and molasses.

6. A method for preparing solid waste-based 3D printing concrete according to any one of claims 1 to 5, characterized in that: The steps include: S1. Mix cement, mineral powder and modified tungsten tailings powder to obtain a cementitious material component A; S2, mixing steel slag, tungsten tailings, dispersible latex powder, early strength agent, retarder and composite fiber to obtain solid component B; S3, adding water reducing agent and water glass into water, diluting and stirring evenly to obtain liquid component C; S4. First add solid component B and part of cementitious material component A, stir, then add part of liquid component C, mix, then add the remaining cementitious material component A and add the remaining liquid component C at a uniform speed and stir again to obtain 3D printed concrete.

7. The method for preparing solid waste-based 3D printing concrete according to claim 6, characterized in that: The mixing time in step S1 is 35-50s.

8. The method for preparing solid waste-based 3D printing concrete according to claim 6, characterized in that: The mixing time in step S2 is 25-35s.

9. The method for preparing solid waste-based 3D printing concrete according to claim 6, characterized in that: The stirring time in step S4 is 25-35 seconds, and the mixing time is 20-30 seconds.

10. The method for preparing solid waste-based 3D printing concrete according to claim 6, characterized in that: The stirring time in step S4 is 135-185s.

Citation Information

Patent Citations

  • Material suitable for 3D printing concrete shear wall and preparation method of material

    CN110540394A